Glass structural elements and load-bearing glass structures. Issue 1 (December 2020) - Balyakina, Olga; Vasilyeva, Olga; Smirnov, Vitaly
Abstract: This article provides an overview of scientific and technical literature on the design and calculation of load-bearing structures made of laminated glass. Since glass is one of the most fragile materials, additional control methods are required for the production, installation and operation of glass structures, because one small defect can reduce the strength of the entire structure several times. The analysis of multilayer glass, its calculation and design for use in construction is presented. The thickness, the number of layers, the presence and type of the intermediate layer, all this affects the strength characteristics of the entire glass structure. The problem of the lack of a Russian regulatory and technical base that would regulate the design of load-bearing glass elements, such as columns, beams, shells, etc.